PENGARUH KUALITAS PELAYANAN K-BANK BUKOPIN SYARIAH TERHADAP KEPUASAN MAHASISWA (Studi Kasus Mahasiswa Ekonomi Syariah Universitas Muhammadiyah Bandung 2021-2023) - Ma’arif, Sohibul; Mulyasari, Heni (ASH-SHIDQU: JURNAL EKONOMI SYARIAH, 2025)
This research was conducted to determine the influence of K-Bank Bukopin Syariah Service Quality on Student Satisfaction, with the UMBandung sharia economics study program as the research object. The sampling technique used in this research is random sampling. The population used was 83 with a sample of 83 using a descriptive quantitative approach. The data analysis technique used is a simple linear regression test. The results of the research show that the t-count value of the service quality variable is 8.073 > t table of 1.989 and the significance value is 0.000 < 0.05. And the magnitude of this influence is 44.6% influenced by service quality while the remaining 55.4% influenced by other variables outside that were not identified by the researcher.